STUDENTS' RESPONSES TOWARD TEACHING WRITING DESCRIPTIVE TEXT BY RUNNING DICTATION - Roro Pipih Cahyati; Yanuarti Apsari (PROJECT (Professional Journal of English Education), 2023)
Writing is one of the most important skills in learning or mastering English, and also one of the problems that are often faced by teachers and students. Because some students still have limited motivations to learn and increase their writing skill. One method to solved that problem is running dictation. The research was conducted to the eight grade of Pasundan 1 Cimahi. The Purpose of this research was to identify students’ responses in writing descriptive text by using running dictation. This research used descriptive qualitative research. The result showed that student’s responses have good responses. As a result, this technique could be an alternative technique for teaching writing descriptive text.